Analysis of supply and demand to enhance educational tourism experience in the Smart Park of Yogyakarta, Indonesia - Ani Wijayanti; Janianton Damanik; Chafid Fandeli; Sudarmadji (Economies, 2017)
The Smart Park (also known as Taman Pintar) is a major educational tourist destination in Yogyakarta, which offers a variety of attractions that are very interesting for tourists. The main purpose of tourists visiting Smart Park is to obtain an educational tourism experience. This subjective experience raises specific challenges for Smart Park as it works towards being a competitive destination. The purpose of this study is to analyze the aspects of the educational tourism experience that are affected by tourism demand and supply. Data were collected from surveys that were sent to 150 respondents and were analyzed using path analysis. The results show that tourism demand and supply contributed to the variation of tourism activities by 45.1%, while the remaining was explained by other variables, such as national budget, local budget, ticket sale, and cooperation with some stakeholders. Tourism supply had a higher effect than tourism demand. Tourism demand did not particularly affect tourism experience. However, the results of the path analysis indicate that tourism supply had direct and indirect effects on tourism experience through the variation of tourism activities, with the indirect effect being the most predominant. In the management of Smart Park, there is still a gap between tourism demand and supply, so the tourism experience has not been maximized to its full potential.
Keywords: C12; P46; Z32; 330; educational tourism; tourism supply and demand; experience; tourism activities